Adopt Biodynamic Farming for sustainable agriculture - Aswal, J S; Sha, Binita; Uniyal, D P (Indian Farming, 2017)
Biodynamic farming is seen as an alternate form of agriculture, meantto avoid health hazards caused by increasing use of agrochemicals. It is an advanced, ecofriendly practice based on principles of soilbiotechnology and microbiology.